2004
DOI: 10.1097/01.bcr.0000144524.11034.59
|View full text |Cite
|
Sign up to set email alerts
|

Gas Fireplace Contact Burns in Young Children

Abstract: Contact burns from domestic appliances are common in young children. Recently, gas fireplaces have been recognized as a potential cause of contact burns in young children. We sought to quantify the frequency of gas fireplace contact burns in young children, to identify the etiology of contact, to describe the clinical presentation, and to describe clinical outcomes. Children with gas fireplace contact burn injuries presenting to The Hospital for Sick Children in Toronto (1999-2002) were identified using three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…These burns occurred most frequently in babies and toddlers, as previously noted in the literature. [5][6][7][8][9] In this review, some older children were also injured, indicating that the injury is not confined to toddlers. These burns were painful to the child and caused disruption in the family's schedules.…”
Section: Discussionmentioning
confidence: 99%
“…These burns occurred most frequently in babies and toddlers, as previously noted in the literature. [5][6][7][8][9] In this review, some older children were also injured, indicating that the injury is not confined to toddlers. These burns were painful to the child and caused disruption in the family's schedules.…”
Section: Discussionmentioning
confidence: 99%
“…No patients in that series required secondary surgery for contractures. Similarly, Zettel et al [13] also found that in 27 children who sustained contact burns from fireplaces, only 3 (11%) required acute excision and grafting. The outcomes in both of these studies were generally good.…”
Section: Discussionmentioning
confidence: 99%
“…De-identified demographic, burn injury, financial (hospital charges), and follow-up data were extracted by each site and entered into a centralized REDCap database collection tool. 9 Burn injury data included place of burn occurrence, anatomic location of burn, and depth of burn (either directly from the chart or inferred from the percentage that required grafting). Hospital data included length of stay, surgical data, therapy data, and complications.…”
Section: Methodsmentioning
confidence: 99%